FINANCIAL RATIO ANALYSIS AND COMMON SIZE TO ASSESS FINANCIAL PERFORMANCE AT PT ASTRA AGRO LESTARI TBK AND ITS SUBSIDIARIES - Sihombing, Rista; G. Maffett, Mark; Nur Ilham, Rico (PT. Radja Intercontinental Publishing, 2022)
From the financial statements can find out how the financial performance of the company. Financial ratio analysis and common size analysis can produce useful conclusions. This study aims to determine the financial performance of PT. Astra Agro Lestari Tbk (PT. AALI) which refers to the balance sheet and income statement for 2020-2022 using financial ratios and the common size method. The research method applied in this research is using descriptive research with a quantitative approach. The results of the research conducted showed that the performance of PT. Astra Agro Lestari Tbk in covering its current liabilities with current assets can still be said to be quite good. From the Gross Profit Margin ratio of PT. AALI Tbk experienced a fairly large increase, namely 4.09%. From the results of the calculation of the common size method at PT. AALI Tbk which is listed on the Indonesian stock exchange in 2020-2021, shows that it allocates more of its funds to fixed assets. In using its capital PT. AALI Tbk uses its equity more than liabilities. There is an increase of 3.75% in the common size of the company, which explains that the company is getting better in terms of profitability.